Hypercholesterolemia - Ashok Kumar, Sekar (IntechOpen, 2015)
This book is aimed to accentuate the importance of hypercholesterolemia, since targeting and treating the hypercholesterolemia is increasingly well known as an essential strategy in the prevention of atherosclerosis-induced cardiovascular disease. It is important to look at hypercholesterolemia as it is proved to be crucial as well as the early stage of atherogenesis and can also be managed with appropriate treatment. This book describes the basics of hypercholesterolemia and its causes and various experimental animal models to understand and study the pathophysiology of hypercholesterolemia as well as to present practice-based clinical approaches to treat hypercholesterolemia. Further, the book describes various treatment strategies of hypercholesterolemia in detail, especially the appropriate use of statin. It is well known that the use of statin is an ideal as well as a potent therapy to lower cholesterol level and also has various beneficial pharmacological effects to prevent cardiovascular diseases. However, there exists less awareness about the use of statin. Hence, it is important to understand the appropriate use of statin in terms of doses for different stages of hypercholesterolemia, side effects, resistance of its use, and also interaction of statin with other drugs, which are well described in this book. In short, the major aim of this compendium is to present to the readers comprehensive, updated, and current research perspectives on hypercholesterolemia.